Performance of Soil Water Content Using Ground Penetrating Radar with Different Antenna Frequencies - Izzati Abd Karim, Nurul; Albati Kamaruddin, Samira; Che Hasan, Rozaimi (International Journal of Engineering and Technology, 2018)
Accurate measurements of Soil Water Content (SWC) with applicable and relevant support are essential in many fields of earth and soil engineering research. Ground Penetrating Radar (GPR) is a geophysical tool that measures and provides accurate results for determination of the SWC. To prove the accuracy of SWC measurement using GPR, a field survey was performed in peat soil. This paper presents a fieldwork survey with the aim of assessing the SWC measurement using GPR. The survey work was conducted at Johor Bharu using different antenna frequencies (250 and 700 MHz). Five profiles, which is 5m by 5m in length, were scanned along an east-west direction with a common offset at an equal spacing of 1m. Â To measure the SWC using GPR, the researchers used the velocity from the GPRâ€™s signal from the receiving antenna to the soil. Statistical analysis was carried out based on the dielectric permittivity and SWC. Schaapâ€™s equation and Rothâ€™s equation were used to distinguish the relative dielectric permittivity of the soil to SWC. The results of this study show the linear function, Â for the measured SWC. The validation graph shows that at a frequency of 250 MHz, the depth of penetration was greater compared to the frequency of 750 MHz. These results, suggest that a higher frequency will give higher resolution but lower depth penetration.Â Â